TEACHING LOAD OF ACCOUNTING INSTRUCTORS. - Knowles, Asa S.; White, William C. (The Accounting Review, 1940)
College teachers and administrators everywhere are very sensitive to real or imaginary inequalities in their teaching loads. Among them probably none is more justified in expressing concern over this matter than the teacher of accounting. He is keenly aware that his elementary courses are the backbone of most business administration programs, while the advanced offerings in his field are perhaps more truly professional than any other single group of business college courses. The almost universal practice is to measure faculty loads in terms of the semester hour, or, a modification of the student credit hour in combination with clock hours for the non-teaching load. In search of a successful method of teacher load evaluation for accounting and other subjects, the writers first reviewed the literature in the field and then turned to an examination of industry's techniques for applying scientific methods to problems of personnel. Authors appreciate that many readers may feel that the scientific advantages of this proposed method of teacher load evaluation suggested here are more than offset by the demands on both time and care required for its successful use.